Integrasi Universal Design for Learning dalam Pendidikan Islam untuk Mewujudkan Pembelajaran Inklusif dan Berkeadilan - Khoirul Irul Anam; Haidar Idris; Moch Mahsun; Nurhafidz Ishari (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2026)
This study explores the potential of Universal Design for Learning (UDL) as a framework for transforming Islamic education by promoting inclusivity and equity. Using a qualitative research approach with a multiple case study design, data were collected through semi-structured interviews, classroom observations, and document analysis in selected Islamic educational institutions. The findings indicate that the implementation of UDL principles significantly enhances student engagement, accessibility to learning materials, motivation, and participation. Moreover, UDL aligns with core Islamic educational values such as justice (‘adl), compassion (rahmah), and respect for learners’ dignity. This study concludes that integrating UDL into Islamic education curricula is a strategic approach to fostering inclusive and equitable learning environments and contributes to ongoing discussions on inclusive educational reform within religious education contexts.